2015
DOI: 10.1093/humupd/dmv030
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and genetic clues for molecular mechanisms involved in uterine leiomyoma development and growth

Abstract: Menstrual cycle-related injury and repair and coinciding hormonal cycling appears to affect myometrial stem cells that, at a certain stage of fibroid development, often obtain cytogenetic aberrations and mutations of Mediator complex subunit 12 (MED12). Mammalian target of rapamycin (mTOR), a master regulator of proliferation, is activated in many of these tumors, possibly by mechanisms that are similar to some human fibrosis syndromes and/or by mutation of upstream tumor suppressor genes. Animal models of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
112
1
10

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(132 citation statements)
references
References 282 publications
(348 reference statements)
4
112
1
10
Order By: Relevance
“…Some patients suffer from leiomyoma, apart from hysterectomy, and most therapeutic treatments only provide temporary effectiveness [12]. Postoperative complications can be relieve by using conventional medical treatment, but the cost related to ULs is considerable.…”
Section: Introductionmentioning
confidence: 99%
“…Some patients suffer from leiomyoma, apart from hysterectomy, and most therapeutic treatments only provide temporary effectiveness [12]. Postoperative complications can be relieve by using conventional medical treatment, but the cost related to ULs is considerable.…”
Section: Introductionmentioning
confidence: 99%
“…The primary reason for this is that the mechanism of pathogenesis is not clear. The formation and development of the tumor is a multifactorial, multi-stage and a gradual process; early diagnosis and timely intervention are essential for the prognosis of patients (5). In previous years, the associations between cell proliferation and cell signaling have become an area of interest (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Brakhta et al reviewed the role of Vit D in uterine biology and found that Vit D deficiency has been associated with increased leiomyomatosis in afro-american group as found by other workers like Baird et al [57,58] which is associated with decreased Vit D absorption due to increase melanin concentrations associated with decreased Vit D R (VDR) concentrations. They demonstrated 1,25 dihidroxy Vit D acts as an antifibrotic factor inhibiting proliferation of immortalized human uterine fibroid cells HuL M cells [59][60][61] .…”
Section: Role Of Vit Dmentioning
confidence: 85%